Migration Processes in the Trans-Dniester Region of the Republic of Moldova and Their Impact on the Socio-Economic Situation - A. Chebanova, Lydia; A. Novikova, Lyudmila; K. Ushakova, Lyudmila; A. Karnilovi, Irina (International Journal of Engineering and Technology, 2018)
The purpose of the study is revealing the content and causes of migration processes in Trans-Dniester Region and their impact on the socio-economic situation in the region. From this perspective the main objectives of the study consisted in disclosing the reasons of considerable population outflow over the past two decades, the study of the peculiarities of different forms of migration in Trans-Dniester Region, identifying trends in migration of population, regulation of the migration mechanism at the present stage, the assessment of the current system of migration flows accounting in Trans-Dniester Region and the definition of its optimization directions. Particular attention is paid to the consideration of the migration scale and the main areas of emigration. The loss of immigration attractiveness of the region and outflow of highly qualified young and active population from Trans-Dniester Region causes a steady reduction in the population, creates a significant imbalance in the demographic structure of the population (in terms of age and profession). Besides, the Trans-Dniester Region turned out to be actively involved in migration processes due to its relative geographical proximity to both Russia and the EU countries. Currently, the predominant role is played by labor migration.Â